Reforms of corporate governance codes in Bangladesh: Developments and future directions - Md Tariqul Islam; Mahfuzur Rahman; Shrabani Saha (Journal of Risk and Financial Management, 2022)
This research investigates corporate governance (CG) norms in Bangladesh, a developing nation. This study assesses the codes' key aspects and how they have evolved since the first code was released in 2006. This analysis shows that BSEC changed its recommendations from voluntary to mandatory in the subsequent revisions in 2012 and 2018. The modified versions increased board independence compared to the original code, although it is still lower than in some other emerging nations. Recent changes to the rules include conditions on the nomination and remuneration committees, along with some other amendments. However, critical governance components, such as choosing an independent board member as chair, improving board independence, and assuring gender diversity, could be implemented in future code development. It is believed that investors would be more interested in Bangladesh's capital market if the policymakers could make the proposed modifications in accordance with the distinctive institutional features of an emerging economy.
Keywords: 650; Bangladesh; corporate governance reform; developing country; voluntary and mandatory rules